Odpowiedzi

2010-03-18T22:19:55+01:00
A) 5x+3x-2x=5-2+4x
6x=3+4x \-4x
2x=3
x=1,5
Najlepsza Odpowiedź!
2010-03-18T22:20:39+01:00
A)5x+3x-2x=5-2+4x
6x-4x=3
2x=3
x=⅔

b) 8(x-2)-5=4-3(x+1)
8x-16-5=4-3x-1
8x+3x=4-1+16+5
11x=24
x=2 3/11

c) 2=4x-3+5x-8-6x-3
-4x-5x+6x=-3-3-2
-3x=-4
x=¾

d) 2(x-1)-3(3x+2)+4(x+5)=0
2x-2-9x-6+4x+20=0
-3x=-20+2+6
-3x=-12
x=4

e)5-3(4-2x)+3+2(5-x)=0
5-12-6x+3+10-2x=0
-6x-2x=-5+12-3-10
-8x=-6
x=8/6=1⅓

f) 8(x-4)+9-3(x+5)+38=0
8x-32+9-3x-15+38=0
5x=-38+15-9+32
5x=0
x=0
2010-03-18T22:25:46+01:00
A)5x+3x-2x-4x=5-2
2x=3/:2
x=1i 1/2

b)8x-16-5=4-3x-3
11x=22/:11
x=2

c)2+3+8+3=3x
16=3x/:3
5i1/3=x

d)2x-2-9x-6+4x+20=0
-3x+12=0
12=3x/:3
4=x

e)5-12+6x+3+10-2x=0
3=-4x/:-4
-3/4=x

f)8x-32+9-3x-15+38=0
5x=0
x=0